L’organisation de cooperation de Shanghai (OCS) dans la Nouvelle Asie: une generalisation d’apres-guerre? . (Халықаралық қатынастар және халықаралық құқық сериясы, 2021)
This article analyzes the concept of «New Asia» and the role of the SCO on it. The emergence of the “Shanghai spirit” сconsidered in the context of a strategic change in the post-bipolar period. The purpose of the article is to demonstrate the main milestones in the formation and development of the SCO and to study its potential as a regional system that fills the strategic vacuum in the Eurasian space. Special attention paid to the expansion of the SCO, the role of its partners and observers. This analysis proves that a platform for discussion and common decision-making is being created.Article attempts to give a conceptual framework of the concept of “New Asia” in the context of an analysis of the process of searching and developing solutions of common interest throughout this global space. A study of the political results of the SCO development process reveals SCO has no hostile intentions, but on the contrary creates an Asian space for member states. The space where the process of regional construction of neighboring states, the construction of a sustainable one, with which one can count on the search for common solutions and the subsequent implementation of common tasks are underway. At the same time, cooperation with the structures created earlier is also developing. In Europe, regional cooperation began after the Second World War, in African countries after the process of decolonization, Latin America has been in search of regional identity for a century and a half since its decolonization.One of the conclusions of this article is that the new Sino-post-Soviet Asia after the Cold War has a common historical and political basis for the formation of the region. A particular institutional illustration of this process is seen through the influence of the SCO. The SCO confirms the emergence of New Asia within the existing conceptual and contextual framework and offers other hypotheses to designate a modern region beyond Asia. The article raises a controversial question – what effective evidence of a causal relationship between post-war regionalization and regionalization of recent decades can be cited?Key words: SCO, “New Asia”, regional construction, cooperation.